Rediscovery of the type specimen of Hadronotus montanus Kieffer, 1906 (Hymenoptera: Scelionidae). (2nd July 2020) - Popovici, Ovidiu Alin; Kamalanathan, Veenakumari
ABSTRACT: The holotype of Hadronotus montanus Kieffer 1906 was discovered in the collection of Hungarian Natural History Museum (Budapest). This species is transferred in Calotelea Westwood, re-described and illustrated.